(untitled) (Journal of Medical & Health Sciences Review, 2025)
This study examined the accumulation of copper, lead, and cadmium in muscle, liver, and kidney tissues from the fish samples. It was taken from Wallago attu (Mullee) in Khanki Headworks on the Chenab River, Pakistan. Results showed that the highest concentrations of copper were in the liver (20.17 ppm), then in the kidneys (7.46 ppm) and muscles (6.70 ppm). Cadmium’s highest level was found in the kidneys (1.55 ppm) due to its role in filtering, unlike lead, which was similar in almost all organs. An analysis of data by gender revealed that male and female fish accumulated the metals at similar rates, suggesting that they took up metals similarly. The estimated daily intake approach and target hazard quotient found that copper intake is safe. The levels of cadmium and lead are higher than recommended, making them unsafe for health. Although the combined hazard index indicated no immediate non-carcinogenic risk, continuous monitoring is essential due to the metals’ bioaccumulative properties. These findings highlight ongoing anthropogenic pollution from industrial, agricultural, and urban sources impacting the Chenab River ecosystem. The study underscores the urgent need for effective pollution control measures, regular biomonitoring, and public awareness to protect aquatic life and ensure the safety of fish consumed by local communities.